Assessment of the effect of maternal health education on danger signs recognition among women in Ifako Ijaiye, Lagos State - Halimah Nuhu Sanda; Nazeef Mohammed; Musa Zakka; Usman Iliyasu; Aliyu Ibrahim Shehu; Abba Rabi’u Hussain; Usman Bashir; Ibrahim Ibrahim Kurba; Musa Isma’il; Aisha Aliyu Ibrahim; Aisha Aliyu Abulfathi (International Journal Of Community Medicine And Public Health, 2026)
Background: Maternal mortality remains a significant challenge in low- and middle-income countries, particularly in Nigeria. Maternal mortality is often attributed to various factors, including delays in seeking care due to a lack of awareness regarding danger signs during pregnancy and childbirth. This study aimed to assess the effect of maternal health education on danger signs recognition among women in Ifako Ijaiye, Lagos State, Nigeria. Methods: A pre-test post-test quasi-experimental design was employed, involving 80 women of reproductive age (40 in the intervention group and 40 in the control group). Participants' baseline knowledge of maternal danger signs was assessed using structured questionnaires. The intervention group received a training package on maternal danger signs. Follow-up assessments were conducted one-month post-intervention to measure changes in knowledge. Results: The mean age of participants was 34.2±7.6 in the control group and 30.4±6.8 in the intervention group. Most participants had secondary education, were self-employed and married. At baseline, there was no significant difference in the mean number of danger signs recongnized between the groups (mean difference=0.225, t (78)=0.565, p=0.574). Post-intervention, the intervention group showed a significant increase in the recognition of maternal danger signs (mean difference=3.70, t (78)=7.13, p=